Economic Inequality and the Spatial Distribution of Stop and Search: evidence from London - Suss, Joel (The British journal of criminology, 2023)
We analyse the spatial concentration of stop and search (S&S) practices. Previous work argues that the persistent reliance on S&S, despite weak to null deterrent effects on crime, results from a social order maintenance motivation on the part of the police. Expanding previous studies that focused on who tends to be stopped and searched by police officers, we focus on where S&S concentrates and investigate the role of economic inequality. We use data from London in 2019 and demonstrate that a novel measure of salient, spatially granular economic inequality is positively associated with S&S incidence at a small spatial scale, even when controlling for crime rates and other important variables. Police officers more frequently stop and search members of the public in places where the well-off and the economically precarious co-exist. Implications for understanding S&S as a tool that distinguishes between citizens, between those to protect and potential criminals, are discussed.